Finite elements and approximation - Zienkiewicz, O. C. (Dover Publications, 2006)
A powerful tool for the approximate solution of differential equations, the finite element is extensively used in industry and research. This book offers students of engineering and physics a comprehensive view of the principles involved, with numerous illustrative examples and exercises. 1983 edition.
Keywords: Approximation theory.; Finite element method.; elektronické knihy; electronic books